Insignificant Variation of Raised Thyroid Stimulating Hormone Level Among Third Trimester of Pregnancy in Diagnosing Subclinical Hypothyroidism (Medical Forum Monthly, 2023)
Objective: To determine and compare the mean values of thyroid stimulating hormone in three trimesters of pregnancy, coming for antenatal workup in Al-Nafees medical college & Hospital Islamabad, Pakistan. Study Design: Descriptive / Analytical study Place and Duration of Study: This study was conducted at the Gynecology/Obstetrics and Pathology departments of Al-Nafees Medical College & hospital Islamabad from 1st Feb, 2018 to 31st Jan, 2019. Materials and Methods: In this study random screening of 150 pregnant females for serum TSH levels was done to identify cases of SCH. Females were divided in to three equal groups i.e. 50 females in first, second and third trimester each. We measured serum TSH levels by using ELISA and take American thyroid association guidelines (ATA) for TSH levels in three trimesters as reference values. Trimester specific cut off values of TSH as given by ATA guidelines were used for diagnosis of cases of SCH. Data were analyzed by SPSS version 20. The study design was cross-sectional. Results: In our study we found a statistically insignificant variation of serum raised TSH amongst three trimesters as depicted by p-value >0.05. Conclusion: It may be inferred from above mentioned results that there was no significant variation seen in TSH levels of patients with subclinical hypothyroidism in our local setting (females coming to ANMC&H for antenatal care) amongst three trimesters. Results of this study suggest that a single TSH value irrespective of trimester specific cut offs can be used to label a female as having SCH. Timely diagnosis will help clinicians to avoid maternal and fetal poor outcomes associated with SCH as documented in various studies on thyroid disorders.